Drama queen [compact disc] - Menzel, Idina (BMG Rights Management, 2023)
The voice behind the highest-grossing animated film of all time, Frozen, Idina Menzel is a 3x Tony Award Nominee and Tony Award Winner. Her upcoming dance project showcases her powerhouse vocals on soaring anthems, disco-infused beats, and the right amount of drama.